A rare case of osteoblastoma of the mandible. Issue 6 (November 2015) - Miyajima, Daisuke; Ishikawa, Ayataka; Yagihara, Kazuhiro; Ishida, Tsuyoshi; Yagishita, Hisao; Kasturano, Miki; Sumimoto, Wakako; Ishii, Junichi
Abstract: Osteoblastoma is a rare bone-forming tumor, accounting for approximately 1% of all primary bone tumors. It commonly affects males within the age range of 10–30 years and typically arises in the vertebral column and long bones. Clinically, patients have pain and swelling. Osteoblastoma of the jawbones is rare, and thus, little is known about it. Here we report a rare case of osteoblastoma of the mandible in a 28-year-old pregnant female with a past history of tooth extraction. The patient experienced slight discomfort in the right mandible approximately 2 years after mandibular third molar extraction. Radiographic examination revealed a mixed radiolucent/radiopaque lesion in the mandible during pregnancy. The lesion, which measured approximately 2.5 cm in diameter, was not associated with the adjacent molar root. Although there was no significant change in the state of the lesion during pregnancy, severe jaw pain and swelling occurred shortly after parturition. Surgical excision was performed and a histopathological diagnosis of osteoblastoma was made. The severe jaw pain completely disappeared after surgery. The patient was followed up for a year and a half and was disease-free. In consideration of the drastic change in symptoms, we speculate that tooth extraction and parturition might have some effect on the progression of osteoblastoma.